Laryngeal mask, alternative in the oxygenation apneica during simpatectomía thoracic. Case Presentation - Diana Elizabeth Benalcázar Villacreses; José Julio Ojeda Gonzalez; Lianet Ojeda Delgado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The case of a 15 year-year-old female patient is presented, attended at the Children's Hospital of Cienfuegos, who reported that since childhood has diaphoresis (profuse sweating) on her body and very noticeable hands and armpits, which prevents proper perfomance in public and the inability to write on paper without it getting wet. He was diagnosed with hyperhidrosis and it was decided to perform video-laparoscopic surgery for thoracic sympathectomy. General anesthesia was used; a laryngeal mask and apneic oxygenation were used to permeabilize the airway, with which hemodynamic stability was achieved. The patient did not present complications and a definitive solution of hyperhidrosis was achieved.